A phase II open‐label study of the intravenous administration of homoharringtonine in the treatment of myelodysplastic syndrome. (23rd May 2013) - Daver, N.; Vega‐Ruiz, A.; Kantarjian, H.M.; Estrov, Z.; Ferrajoli, A.; Kornblau, S.; Verstovsek, S.; Garcia‐Manero, G.; Cortes, J.E.
<x xml:space="preserve">Abstract</x> Homoharringtonine is an alkaloid inhibitor of protein synthesis with activity in myeloid malignancies. We report a phase II pilot study of homoharringtonine in myelodysplastic syndrome (MDS). Induction consisted of homoharringtonine at 2.5 mg/m2 via continuous infusion for 7 days. Maintenance was given every 4 weeks. Nine patients were enrolled: five with refractory anaemia with excess blasts, two with refractory anaemia with excess blasts in transformation, one each with refractory anaemia and chronic myelomonocytic leukaemia respectively. Median age was 70 years (55–84) and 6 (66%) were male. Per International Prognostic Scoring System (IPSS) two patients were intermediate‐1, five intermediate‐2 and two high‐risk. Median chemotherapy courses were one (1–3). One patient (11%) responded with complete haematological and cytogenetic remission after one course. Eight patients did not respond (four had stable disease, two progressed to acute leukaemia and two died during induction – from aspergillus pneumonia and intracerebral haemorrhage respectively). Grade 3/4 myelosuppression seen in 56% (5/9). Serious non‐haematological toxicities included one case of grade 4 left bundle branch heart block and one grade 3 nephrotoxicity. Median time between courses was 42 days (35–72 days). In conclusion homoharringtonine might have clinical activity in some patients with MDS.